Polydipsia and autistic traits in patients with schizophrenia spectrum disorders - Komatsu, Hiroshi; Ono, Takashi; Onouchi, Yuji; Onoguchi, Goh; Maita, Yoshinori; Ishida, Yusuke; Maki, Takahiro; Oba, Akiko; Tomita, Hiroaki; Kakuto, Yoshihisa (Frontiers in Psychiatry, 2023)
Polydipsia, prevalent in 6%-20% of patients with schizophrenia, results in seclusion and prolonged hospitalization. It is also observed in autistic individuals, with previous studies reporting that autism accounted for 20% of all hospitalized patients with polydipsia. The current study investigated the association between polydipsia and autistic traits in patients with schizophrenia spectrum disorders (SSDs) based on the hypothesis that higher autistic traits would be observed in schizophrenic patients with polydipsia. In the first study (study A), the Autism-Spectrum Quotient ((AQ; Japanese version) scores of long-stay inpatients with and without polydipsia were compared. Furthermore, the association between polydipsia and autistic traits was also examined in short-stay inpatients and outpatients with SSDs (study B). Study A showed that patients with polydipsia scored significantly higher on the three AQ subscales (attention switching; communication; and imagination) compared to those without. Study B also showed that patients with polydipsia had significantly higher AQ scores overall and for several subscales compared to those without polydipsia. Binary logistic regression analysis of the combined sample showed that male gender and higher autistic traits were significant predictors of polydipsia. The study highlights the importance of focusing on such traits to understand the pathogenesis of polydipsia in SSD patients.